Oral traditions and aesthetic transfer : form and social vision in black poetry / Charles Bodunde. - Bodunde, Charles (Bayreuth University African studies ;, 2001)
Charles Bodunde's work reveals that the revitalisation of the oral idiom does not arise from a nostalgic longing for local folklore colour for 'postcard poetry'. They reintroduce the oral idiom to recreate poetic language.